Utility analysis of outpatient hypertensive patients with and without comorbidities using the EQ-5D-5L instrument: A study at UPTD Puskesmas Pagerageung, Tasikmalaya Regency, West Java - Priatna, Muharam; Maulida, Putri Salma; Alifiar, Ilham (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
Hypertension is a chronic condition often requiring lifelong treatment, which can impact patients’ quality of life (QoL) in physical, psychological, and social domains. The presence of comorbid conditions alongside hypertension can further deteriorate QoL. Health utility measurement, particularly in hypertensive patients with comorbidities, is crucial for understanding these compounded effects. This study aims to evaluate and compare the quality of life utility in hypertensive patients with and without comorbidities using the EQ-5D-5L instrument, focusing on how comorbid conditions influence overall QoL. A descriptive observational study with a cross-sectional design was conducted among 100 hypertensive patients treated at UPTD Puskesmas Pagerageung, Tasikmalaya, from January to March 2024. Participants were selected through purposive sampling. The EQ-5D-5L questionnaire was used to assess utility scores, which were calculated using an Indonesian-specific value set. Chi-square and Post Hoc LSD analyses were applied to explore relationships between utility scores and demographic factors such as age, gender, and occupation. The average utility score for hypertensive patients without comorbidities was 0.669, higher than that of patients with comorbid conditions. Specifically, patients with diabetes mellitus, osteoarthritis, gastric conditions, heart disease, and severe comorbidities (e.g., kidney disease, cataracts, stroke) had average scores of 0.578, 0.640, 0.651, 0.537, and 0.148, respectively. Age was significantly associated with utility scores (p = 0.014), whereas gender and occupation showed no significant impact. Hypertensive patients without comorbidities had a better quality of life utility than those with additional health issues. Targeted management of comorbidities is essential to improve the quality of life among hypertensive patients, especially in those facing compounded health challenges.